Tailored porosity from waste biomass: mesoporous bio-adsorbents for targeted treatment of complex industrial wastewaters - Toor, Saqib Sohail; Sharma, Kamaldeep; Klemmt, Rebekka; Mamakhel, Mohammad Aref Hasen; Achour, Abdenour (Frontiers in Fuels, 2026)
The valorization of waste biomass into tailored adsorbents presents a sustainable strategy for combating industrial water pollution. This study highlights the critical role of precursor morphology in determining the textural properties and function of bio-adsorbents derived from wheat straw (WS) and the organic fraction of municipal solid waste known as biopulp (BP). Through carbonization and KOH activation, the fibrous WS was transformed into a microporous, high-surface-area activated wheat straw (AWS) bio-adsorbent, while the compact BP yielded a mesoporous network in activated biopulp (ABP). This structural difference affects adsorption performance: AWS demonstrated superior efficacy in batch removal of phenols (93.2%) and total organic carbon (85%) from the complex hydrothermal liquefaction aqueous phase (HTL-AP), whereas ABP excelled in treating produced water (PW), achieving >95% removal of organic pollutants. Continuous fixed-bed column studies confirmed the scalability of AWS for HTL-AP treatment, revealing distinct breakthrough dynamics between bulk parameters and specific contaminants. This work provides evidence supporting precursor-dependent tailoring of pore structure for targeted wastewater treatment, providing a possibility for a circular and sustainable solution for the treatment of complex industrial wastewaters.